Konsep Dan Kontribusi Pemikiran Adiwarman Azwar KarimTerhadap Perekonomian Indonesia - Fatkhul Wahab (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2016)
Discourse on Islamic economics was intoduced by classical theologian before. But, Islamic economics had an ups and down experiences that eventually disappeared and replaced by the conventional economic system that doesn‘t touch the Islamic teaching, resulting the conventional economic ignoring the community welfare and give the benefit for a few people, they are the owners of capital.Indonesia is no different from other countries in the implementation of the economic system,although the theory presented policy holders of this country is based on Pancasila economy populist, but in practice, instead of applying the conventional economy. Unavoidable, that the Kiblat of the national economy is the developed countries that implement economic system by individulist-liberlist character.Islamic economic in Indonesia can not be separated from the contribution of Adiwarman Azwar Karim. He offers a concept that the Islamic economic is the economy system which built on the universal values of Islam. The mean values are unity (tauhid), justice ('adl), government (khilafah), prophethood (nubuwwah), and return (ma'ad). This article examines the concept and contribution Adiwarman Azwar Karim to Indonesia economic system. Researcher concluded that the Islamic economics offered by Adiwarman Karim takes a historical and jurisprudence approach. His contribution in developing the concept of Islamic economics aims to find solutions to a growing problem in society.